Data Fusion Algorithm of Power Line Carrier Communication Based on Minimum Spanning Tree Theory. Issue 1 (April 2020) - Lu, Hai; He, Ziyang; Pen, Haibo; Yang, Ting
Abstract: With the expansion of the clean energy photovoltaic power generation systems, the requirements of communication and data exchange capacity become higher and higher. The status information of each photovoltaic unit should be collected. However, when the number of PV units is too large or the collection frequency is too high, it will generate huge amount of data to the communication system. If each monitoring terminals transmits the data to the master station independently, the huge traffic flows occupy bandwidth and reduce the communication efficiency, which also affect the real-time monitoring of the photovoltaic system. To solve this problem, this paper proposed a novel data fusion algorithm for power line carrier communication based on minimum spanning tree transmission path. The data fusion packet format is also presented. Finally, the effectiveness of the proposed algorithm is proved by comparing the amount of data brought by the fusion algorithm and the non-fusion algorithm.